1972
DOI: 10.1042/cs0420345
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Rebreathing Methods for Measuring Mixed Venous P co2 During Exercise

Abstract: 1.Measurements have been made of mixed venous Pco, (PV,co,) by two methods during exercise at 50 and 100 W in five adult male subjects.2. The equilibration (plateau) method and the extrapolation (Defares) method were performed alternately, five times each, during the steady-state exercise.3. The coefficient of variation of PT,co, by the extrapolation method was much higher than that of the plateau method. The PJ,co, can be estimated to within f 1 mmHg by the plateau method, and the derived cardiac output to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

1977
1977
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 8 publications
3
16
1
Order By: Relevance
“…37 End tidal tension of CO 2 (P ET CO 2 ) was used to estimate arterial CO 2 tension (P A CO 2 ), and Godfrey's recommendations were used to estimate CO 2 content. 38 This combination has been found to give highly reproducible results (coecient of variation 5.7%) during submaximal exercise in healthy individuals. 20 The results are also in agreement with the results obtained by the direct Fick method 39 and the dye dilution method.…”
Section: Discussionmentioning
confidence: 87%
“…37 End tidal tension of CO 2 (P ET CO 2 ) was used to estimate arterial CO 2 tension (P A CO 2 ), and Godfrey's recommendations were used to estimate CO 2 content. 38 This combination has been found to give highly reproducible results (coecient of variation 5.7%) during submaximal exercise in healthy individuals. 20 The results are also in agreement with the results obtained by the direct Fick method 39 and the dye dilution method.…”
Section: Discussionmentioning
confidence: 87%
“…MUIESAN et al (1968) reported that good agreement was observed between both ox-PVCO2 values. However, GoDFREY and WOLF (1972) reported that the plateau method gave several Torr higher ox-PVco2 values than the extrapolation method. Actually, it is fairly difficult to obtain consistent values for tr-and ox-PVco2.…”
Section: Discussionmentioning
confidence: 98%
“…The alternative, equilibrium method, has been thought to be more reliable than the exponential method [9], but recently the application of computer analysis to the exponential method has im proved its precision [13]. A number of methods have been proposed for the derivation of the asymptote of the exponential rise in PCO2 in the rebreathing system.…”
Section: Methodsmentioning
confidence: 99%
“…Rebreathing is used to obtain PvC02 and PaCC>2 is estimated from rapid CO2 analysis of end-tidal gas during air breathing. Of the two methods available for estimation of PvCC>2, the equilibrium method, in which a high initial concentration of CO2 is rebreathed [4,20], has been thought to be more reliable [9] than the exponential method, in which a low concen tration of CO2 is rebreathed [6,16,23], Recently, com puter-assisted analysis of CO2 during rebreathing has Rebreathing may be used to measure mixed venous PCO2 during exercise and derive cardiac output (0) using the Fick principle applied to CO2. In the form of the Fick equation used for this purpose: 0 = VCO2/CVCO2 -CaC02, carbon dioxide output (VCO2) is measured by expired gas collection, and the contents of CO2 in venous (CŸCO2) and arterial blood (CaCCh) are derived from by angina or cardiac arrhythmias.…”
Section: Introductionmentioning
confidence: 99%